Managerial and Disciplinary Constraints Applied to Faculty Staffing - Belanger, Charles H. (Canadian Journal of Higher Education, 1979)
The purpose of this study was to determine whether the same faculty members would be dismissed when faculty staffing decisions were based solely on institutional personnel management constraints as when the decisions were further constrained to preserve disciplinary integrity. Two sets of constraints were entered into an integer linear programming model to assess the effect on the structural integrity of a discipline and on the allocation of faculty resources when a 20 percent budget reduction was simulated. After collecting actual data from six academic departments at Florida State University, the analysis of the results led to the conclusion that each department chairman needed to structure his discipline into discipline elements, determine the basic number of positions essential to given identity to each discipline element, and protect the key specialists who filled those positions regardless of their teaching assignments. The number of such positions must be very limited to avoid losing the financial stability of the department in steady-state conditions and being lock-steppped in times of budgetary restrictions.